Montelukast in the treatment of HIV associated immune reconstitution disease. Issue 6 (6th December 2006) - Hardwick, C; White, D; Morris, E; Monteiro, E F; Breen, R A; Lipman, M
Abstract : The pathogenesis of immune reconstitution disease (IRD) is not well understood and it can be difficult to manage. Leukotrienes exert proinflammatory effects, have an important role in the innate immune response, and are relatively deficient in HIV infection. Montelukast is a leukotriene receptor antagonist (LTRA) currently licensed for the treatment of asthma. We report a series of three patients with severe HIV associated IRD (cases 1 and 2 associated with starting HAART and unresponsive to steroids), who obtained clinically dramatic responses to treatment with montelukast. The first case is of IRD to secondary syphilis and the second and third to tuberculosis. Cases 1 and 3 both relapsed after a temporary break from montelukast and resolved on restarting. Montelukast should be considered in HIV associated IRD as an alternative to steroids and where these are not effective. Leukotriene overactivity may be implicated in IRD.